Uiarnerit. A historical study of immigration from East to West Greenland in the nineteenth century - Jensen, Einar (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2002)
AbstractThis article is about 50 East Greenlanders who settled in the Kap Farvel area in 1887, and about their encounter with the local population, the German Moravian Brethren mission, and the Danish mission and colonial administration. On the basis of this immigration, the article gives an account of a number of new issues and perspectives on settlement and the settlement policy for the overall immigration from East Greenland to South West Greenland and the traces left by these migrations on South West Greenland right up to now. Despite formal status as West Greenlanders, the immigrants and their descendants preserved East Greenlandic features which in many ways still exist, and today people in the area take a great deal of interest in the historical events, the distinctive features of the immigrants and their links with East Greenland. One motive for this study is thus a growing local wish to turn the focus on the migrations from East Greenland and to raise consciousness about their significance for the present-day situation. The following account is intended as a contribution to this consciousness-raising process. The article presents a hitherto unexploited body of historical and ethnohistorical sources which will be used as the basis for a future historical study of the immigration from East Greenland to West Greenland and to improve our knowledge of the cultural, social and other traces of East Greenlanders in South West Greenland, and how these traces were kept.